The relationship between acoustic habitat, hearing and tonal vocalizations in the Antillean manatee (Trichechus manatus manatus, Linnaeus, 1758) - Rivera Chavarría, Mario (2015)
The Antillean manatee (Trichechus manatus manatus) is an endangered marine mammal that inhabits the Caribbean Sea and riverine systems in Central America. Their acoustic behavior is relevant for individual identification, mating and parental care. Manatees produce tonal sounds with highest energy in the second harmonic (usually 5 kHz), and their audiogram indicates sensitivity from 0.3 kHz to 90 kHz with lowest thresholds in the 16 to 18 kHz range.We recorded manatees in the San San River, a highly polluted riverine system in Panama, using a stereo array. Frequency transmission experiments were conducted in four subhabitats, categorized using riverine vegetation. Incidental interactions of manatees and small motorboats were examined. Acoustic transmission was linearly related to tonal vocalization characters: correlations were stronger in freshwater than in transition and marine environments. Two bands, 0.6 to 2 kHz and 3 to 8 kHz, attenuate similarly in all subhabitats, and these bands encompass F0 (tone) and peak frequency respectively of manatee tonal calls. Based on our data we conclude that frequency transmission depends mainly on river depth and bottom characteristics, also motorboat sounds mask signals from 3.5 kHz to 8 kHz, which overlaps the peak frequency of tonal calls. In spite of differences between acoustic transmission in subhabitats of the San San River, manatees utilize bands that transmit efficiently in all subhabitats.